A novel strategy for constructing clustered point mutations. - Haltiner, M (1985)
We have modified the synthetic linker mutagenesis procedure (1,2) in order to facilitate both the construction and the analysis of deletions, insertions and clustered point mutations generated in DNA in vitro. The protocol as originally described by McKnight and Kingsbury (1) involved attaching a synthetic linker sequence to each 5' or 3' deletion endpoint in DNA. We have designed specific plasmid vectors that can be used to generate nested sets of deletion mutations in the DNA being analyzed. The utility of these vectors is that a linker sequence of choice can be inserted at the endpoint of a deletion in a single intramolecular ligation without the use of synthetic linker DNA. In a second modification of the original procedure, we have adopted a rapid method for sequencing supercoiled plasmid DNAs from 10 ml cultures by primer extension. The site-directed mutagenesis strategy outlined here is suited for studying regulatory regions of DNA, such as origins of DNA replication, transcriptional promoters, enhancer elements, and activator binding sites. We have used this rapid and efficient strategy to generate deletions, insertions, and clustered point mutations in the transcriptional control region of a gene encoding the major human ribosomal RNAs.